Bedside Percutaneous Tracheostomy versus Open Surgical Tracheostomy in Non-ICU Patients. (12th January 2014) - Brotfain, Evgeni; Koyfman, Leonid; Frenkel, Amit; Semyonov, Michael; Peiser, Jochanan G.; Hayun-Maman, Hagit; Boyko, Matthew; Gruenbaum, Shaun E.; Zlotnik, Alexander; Klein, Moti
Abstract : Percutaneous bedside tracheostomy (PBT) is a one of the common and safe procedures in intensive care units through the world. In the present paper we published our clinical experience with a performance of PBTs in the regular ward by intensive care physicians' team. We found it safe and similar outcome in comparison to open surgical tracheostomy method in operation room by ENT team. The performance of PBT in the regular ward showed potential economic advantages in saving medical staff and operating room resources.